Characterisation of a solar roof tile (SunSlates™) : with focus on local applicability and conditions - Rautenbach, Karel Frederick (Stellenbosch : Stellenbosch University, 2010)
Project report presented in partial fulfilment of the requirements for the degree of Master of Engineering at the University of Stellenbosch.